Educational thought and ideology in modern Japan : - Horio, Teruhisa (University of Tokyo Press, 1988)
This book is the best work to understand the "making of the modern Japanese". It helped reader immensily to read it The translation of Mr. Platzer is excellent for not only he knows very well Japanese, but he has his own insight into the country psyche: an unconventional, unortodox, unusual, but nevertheless VERY stimulating insight